Myocardial adaption to HI(R)T in previously untrained men with a randomized, longitudinal cardiac MR imaging study (Physical adaptions in Untrained on Strength and Heart trial, PUSH-trial) - Scharf, Michael; Oezdemir, Derya; Schmid, Axel; Kemmler, Wolfgang; von Stengel, Simon; May, Matthias S.; Uder, Michael; Lell, Michael M. (PLOS ONE, 2017)
Objective Although musculoskeletal effects in resistance training are well described, little is known about structural and functional cardiac adaption in formerly untrained subjects. We prospectively evaluated whether short term high intensity (resistance) training (HI(R)T) induces detectable morphologic cardiac changes in previously untrained men in a randomized controlled magnetic resonance imaging (MRI) study. Materials and methods 80 untrained middle-aged men were randomly assigned to a HI(R)T-group (n = 40; 43.5±5.9 years) or an inactive control group (n = 40; 42.0±6.3 years). HI(R)T comprised 22 weeks of training focusing on a single-set to failure protocol in 2–3 sessions/week, each with 10–13 exercises addressing main muscle groups. Repetitions were decreased from 8–10 to 3–5 during study period. Before and after HI(R)T all subjects underwent physiologic examination and cardiac MRI (cine imaging, tagging). Results Indexed left (LV) and right ventricular (RV) volume (LV: 76.8±15.6 to 78.7±14.8 ml/m2; RV: 77.0±15.5 to 78.7±15.1 ml/m2) and mass (LV: 55.5±9.7 to 57.0±8.8 g/m2; RV: 14.6±3.0 to 15.0±2.9 g/m2) significantly increased with HI(R)T (all p<0.001). Mean LV and RV remodeling indices of HI(R)T-group did not alter with training (0.73g/mL and 0.19g/mL, respectively [p = 0.96 and p = 0.87]), indicating balanced cardiac adaption. Indexed LV (48.4±11.1 to 50.8±11.0 ml/m2) and RV (48.5±11.0 to 50.6±10.7 ml/m2) stroke volume significantly increased with HI(R)T (p<0.001). Myocardial strain and strain rates did not change following resistance exercise. Left atrial volume at end systole slightly increased after HI(R)T (36.2±7.9 to 37.0±8.4 ml/m2, p = 0.411), the ratio to end-diastolic LV volume at baseline and post-training was unchanged (0.47 vs. 0.47, p = 0.79). Conclusion 22 weeks of HI(R)T lead to measurable, physiological changes in cardiac atrial and ventricular morphologic characteristics and function in previously untrained men. Trial regristration The PUSH-trial is registered at the US National Institutes of Health (ClinicalTrials.gov), NCT01766791.